Purification, Characterization and Sequencing of Alginate Lyase from Martelella sp. strain MAK4 (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Bacterial isolate MAK4 was isolated from brown algae collected from the coastal area of the Red sea, Hurghada, Egypt and confirmed for alginate lyase production by halo formation around the colonies after flooding with cetylpyridinium chloride or Gramâ€™s iodine. Isolate MAK4 was identified according to morphological, biochemical and phylogenetic identification through 16s rRNA. The bacterial isolate was tentatively identified as Martelella sp. strain MAK4. It is aerobic, mesophilic, Gramâ€“ve, non-spore forming nonmotile, rod-shaped organism and produces catalase and oxidase. PCR was performed for alginate lyase gene using two pairs of degenerate primers. The alginate lyase enzyme was isolated and purified from the culture medium by ammonium sulfate precipitation, Sephadex G-100 and DEAE-Cellulose chromatography. The isolated enzyme has a specific activity of 62.9 u/mg, 6.15 purification folds and has a molecular weight of 35 kDa. The alginate lyase enzyme showed highest activity at 37 Â°C and at pH 7. The enzyme was stable over the pH range 6 to 9 and retained 80% of its activity after incubation at 40 Â°C for 90 min. The enzyme was active in the absence of metal ions, but the activity was enhanced by the addition of NaCl, KCl and Ca2+. The activity was lost with the addition of EDTA. The enzyme activity was strongly decreased in the presence of Cu2+, Zn2+, Co2+, Hg2+ and Mn2+. This novel bifunctional alginate lyase has the potential to be used in the eradication of resistant bacterial biofilm in clinical samples and production of alginate   oligosaccharides in industry.
Keywords: Alginate, purification, alginate lyase, Martelella sp., metal ions